PENGELOLAAN PENDAPATAN ASLI DESA (PADES) OLEH PEMERINTAH DESA KASIA KECAMATAN SUMALATA KABUPATEN G ORONTALO UTARA - Halid, Miman; Kadir, Jusrin; Abubakar Talalu, Mohamad (STISIPOL Mujahidin Buol, 2023)
This research aims to determine the Management of Village Original Income (PADes) by the Kasia Village Government. The research method used is descriptive qualitative. The research results concluded that Kasia Village's PAD management planning was not optimal due to the Village Government's inability to identify village potentials. The implementation of PAD management in Kasia Village is not yet optimal, this can be seen from the way the Kasia Village Government manages village finances which is less than transparent, giving rise to community distrust. Supervision of PAD management in Kasia Village is not yet optimal, this can be seen from several irregularities in village financial management such as the absence of reporting related to village financial traffic flow but no action or steps taken by the Village Consultative Body (BPD)